2016
DOI: 10.1016/j.renene.2015.08.036
|View full text |Cite
|
Sign up to set email alerts
|

A continuous and analytical modeling for kites as auxiliary propulsion devoted to merchant ships, including fuel saving estimation

Abstract: International audienceA performance prediction program dedicated to merchant ships was developed to assess fuel saving abilities of a kite. The solving of the parameterization presented led to kite velocities and tethers tensions prediction continuously along a flight path within the wind window, including especially wind gradient and ship velocity. Both static and dynamic flight cases were considered regarding optimization strategy for kite tow efficiency. For dynamic flight case azimuth, elevation and orient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(60 citation statements)
references
References 8 publications
0
56
0
Order By: Relevance
“…The kite and sail are two main ways of auxiliary propulsion. Successful trials have shown that 30% to approximately 50% fuel savings could be achieved under good wind conditions …”
Section: Mre Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…The kite and sail are two main ways of auxiliary propulsion. Successful trials have shown that 30% to approximately 50% fuel savings could be achieved under good wind conditions …”
Section: Mre Generationmentioning
confidence: 99%
“…Successful trials have shown that 30% to approximately 50% fuel savings could be achieved under good wind conditions. [33][34][35][36] 2. Offshore solar energy Offshore solar energy can be harnessed for heating and photovoltaic generation on ships, offshore platforms, and islands.…”
Section: Novelty Statementmentioning
confidence: 99%
“…In dynamic flight mode the kite is operated perpendicularly to the tether and the kite velocity is a variable. It is possible to use a simple dynamic flight model, such as the zero mass model [6,[12][13][14], to calculate v k as a function of time and to use this in Eq. (4.1) to derive the apparent wind velocity.…”
Section: Relative Wind Conditionsmentioning
confidence: 99%
“…In the last decades, renewable energies have been reintroduced in the shipping industry. These energy sources have been incorporated mainly as a complementary technology, hybridizing traditional fossil fuel-powered systems, see e.g., [3][4][5][6][7][8][9][10][11][12], but some projects substitute fossil fuels completely [13].…”
Section: Introductionmentioning
confidence: 99%